2020
DOI: 10.1186/s41021-020-0146-3
|View full text |Cite|
|
Sign up to set email alerts
|

Genotoxicity assessment of titanium dioxide nanoparticle accumulation of 90 days in the liver of gpt delta transgenic mice

Abstract: Backgound: A variety of in vivo and in vitro studies to assess the genotoxicity of titanium dioxide nanoparticles (TiO 2 NPs) have been reported, but the results are inconsistent. Recently, we reported that TiO 2 NPs exhibit no genotoxic effects in the liver and erythrocytes during a relatively brief period following intravenous injection into mice. However, there is no information about long-term genotoxicity due to TiO 2 NP accumulation in tissues. In this study, we investigated the long-term mutagenic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…TiO 2 NPs (< 30 nm) were administered to male gpt Delta transgenic C57BL/6J mice at doses up to 50 mg/kg bw once a week for 4 weeks, then Pig-a mutation was analysed in erythrocytes and gpt and Spimutation in liver (Suzuki et al, 2016). In another assay performed in the same laboratory the gpt and Spigenes were investigated in liver 90 days after the last injection (Suzuki et al, 2020). Louro et al (2014) treated intravenously C57BL/6 transgenic mice and analysed LacZ mutations in liver and spleen.…”
Section: In Vivo Gene Mutation Studiesmentioning
confidence: 99%
“…TiO 2 NPs (< 30 nm) were administered to male gpt Delta transgenic C57BL/6J mice at doses up to 50 mg/kg bw once a week for 4 weeks, then Pig-a mutation was analysed in erythrocytes and gpt and Spimutation in liver (Suzuki et al, 2016). In another assay performed in the same laboratory the gpt and Spigenes were investigated in liver 90 days after the last injection (Suzuki et al, 2020). Louro et al (2014) treated intravenously C57BL/6 transgenic mice and analysed LacZ mutations in liver and spleen.…”
Section: In Vivo Gene Mutation Studiesmentioning
confidence: 99%
“…Titanium dioxide nanoparticles (TiO2NPs) possess interesting photocatalytic properties, such as the ability to mediate the photolysis of pharmaceuticals, inactivating bacteria, and the effect of photo-oxidative killing on cancer cells, energy storage, in addition to air and water purification, and other uses (2). TiO2NPs are increasingly being manufactured in large quantities for industrial applications such as cosmetics, dyes, foods, and photocatalysts (3). They are used in water, sewage, and gas combustion treatment as an anti-bacterial material for decontamination and a cofactor in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies in rodents exposed to TiO 2 reported toxic effects such as inflammation, impairment of biological barrier functions (intestinal, placental, blood-testis), as well as the promotion of cancer development [ 7 , 10 , 11 ]. Overall, repeated exposure to these particles exhibiting cytotoxic, genotoxic and immunotoxic effects is considered to be an important health issue [ 12 14 ]. For the general population, there is accumulating evidence that the main uptake route is ingestion, since TiO 2 is produced at high volumes as a food grade pigment (E171 in EU) incorporated in many foodstuffs as well as in toothpaste, medicines and food supplements.…”
Section: Introductionmentioning
confidence: 99%